TRBP–Dicer interaction may enhance HIV-1 TAR RNA translation via TAR RNA processing, repressing host-cell apoptosis - Chiaki Komori; Tomoko Takahashi; Yuko Nakano; Kumiko Ui-Tei (Biology Open, 2020)
The transactivating response (TAR) RNA-binding protein (TRBP) has been identified as a double-stranded RNA (dsRNA)-binding protein, which associates with a stem-loop region known as the TAR element in human immunodeficiency virus-1 (HIV-1). However, TRBP is also known to be an enhancer of RNA silencing, interacting with Dicer, an enzyme that belongs to the RNase III family. Dicer cleaves long dsRNA into small dsRNA fragments called small interfering RNA or microRNA (miRNA) to mediate RNA silencing. During HIV-1 infection, TAR RNA-mediated translation is suppressed by the secondary structure of 5′UTR TAR RNA. However, TRBP binding to TAR RNA relieves its inhibitory action of translation and Dicer processes HIV-1 TAR RNA to generate TAR miRNA. However, whether the interaction between TRBP and Dicer is necessary for TAR RNA translation or TAR miRNA processing remains unclear. In this study, we constructed TRBP mutants that were unable to interact with Dicer by introducing mutations into amino acid residues necessary for the interaction. Furthermore, we established cell lines expressing such TRBP mutants. Then, we revealed that the TRBP–Dicer interaction is essential for both the TAR-containing RNA translation and the TAR miRNA processing in HIV-1.